Optimal Tax Rate and Economic Growth : an Empirical Application to the Case of Lebanon - Sayegh, Rosette Ghossoub; Saade, Nisrine Hamdan (DEMO, 2020)
Many studies highlight the significant impact of fiscal policy on the economic growth rate, in countries with a precarious financial and economic situation, similar to the Lebanese case. An empirical study, covering the period 1971-2017, is conducted in this paper, to determine the optimal tax burden that maximizes the economic growth rate in Lebanon. A non-linear relationship between the tax burden and economic growth is examined, using the Scully static model Scully (1996, 2003). Looking at the country ' s periods of political conflict and economic instability, the econometric model estimates lead to an optimal tax burden of 20.62%.(original abstract)